Respons Bifasik dan Modulasi Indeks Aterogenik Ekstrak Etanol Moringa oleifera pada Model Zebrafish Diet-Induced Obesity: Sebuah Evaluasi Farmakologis - Yhusi Karina Riskawati; Aswaty Nur; Dewi Mustika; Budi Hartono; Grace Meigawati Iwanto; Siluh Putu Chinintya Vania Saraswati; Christyaji Indradmojo (Journal of Pharmaceutical and Sciences, 2026)
Background: Obesity-related dyslipidemia is a major cardiovascular risk factor. Moringa oleifera is rich in phytosterols and flavonoids with potential hypolipidemic properties. However, its pharmacodynamic profile and dose-dependent responses in in vivo models remain incompletely understood, particularly regarding hormetic effects associated with crude extracts. Objective: To evaluate the effects of M. oleifera leaf ethanol extract on lipid profile modulation and atherogenic index in a Diet-Induced Obesity (DIO) zebrafish model. Methods: Wild-type female zebrafish were induced with obesity using an Artemia nauplii overfeeding protocol (DIO model) and allocated into five groups (n=9-10 per group analysed): non-DIO control, DIO control, DIO + 0.56 ppm extract, DIO + 1.12 ppm extract, and DIO + 2.24 ppm extract. After 40 days, visceral adipose tissue was collected for colorimetric lipid analysis. The atherogenic index (AI) was calculated as a lipoprotein-ratio-based proxy for cardiovascular risk. Results: DIO induction significantly increased total cholesterol levels and the atherogenic index. Interestingly, M. oleifera extract exhibited a biphasic response. The 0.56 ppm dose significantly restored lipid profiles and reduced the LDL/HDL ratio (AI) to levels approaching those of the non-DIO group (p<0.05), although marked inter-individual variability at this dose warrants cautious interpretation. In contrast, the 1.12 ppm dose failed to improve lipid parameters and instead worsened the atherogenic ratio, tentatively suggesting the presence of a therapeutic window and a possible shift toward pro-oxidant/metabolic stress at higher doses. At the highest dose (2.24 ppm), total cholesterol and AI partially recovered relative to the 1.12 ppm dose; this secondary finding was less consistent than the 0.56 ppm response and requires further study before mechanistic interpretation. Conclusion: M. oleifera ethanol extract demonstrated the most consistent hypolipidemic effect at the lowest dose tested (0.56 ppm) through modulation of the atherogenic index. These findings highlight the importance of dose standardization and further toxicological and phytochemical characterization in phytopharmaceutical development to avoid paradoxical effects and maximize therapeutic efficacy